Trichomonas vaginalis Brain Abscess in a Neonate. (24th October 2017) - Hamilton, Hunter; Pontiff, Kristen L; Bolton, Michael; Bradbury, Richard S; Mathison, Blaine A; Bishop, Henry; de Almeida, Marcos; Ogden, Beverly W; Barnett, Evan; Rastanis, Donna; Klar, Angelle L; Uzodi, Adaora S
Abstract: We describe a case of cerebral trichomoniasis in a neonate in whom seizures and multiorgan failure developed during treatment for staphylococcal sepsis. Brain abscesses were identified with cranial sonography, and Trichomonas vaginalis was isolated from cerebrospinal fluid samples. The patient died despite metronidazole therapy.